Makna Sosial dalam Nilai-nilai Budaya Sunda pada Lakon Wayang Golek Ki Dalang Wisnu Sunarya - Sauky, M. Asfahani; Bukhori, Bukhori (TEMALI : Jurnal Pembangunan Sosial, 2021)
This research is focused Social Meanings in Sundanese Cultural Values in the Wayang Golek Play, Ki Dalang Wisnu Sunarya, especially the Sundanese people are famous for their people who are soméah (friendly), handap asor (courtesy of others), silih asih (loving each other), silih asuh (protecting each other), and silih asah (mutually improving oneself). The aim is to find out Sundanese social meanings and cultural values conveyed through the puppet show. This paper uses a descriptive method. The data source used is primary data from direct interviews of people related to the puppet show. Meanwhile, the researcher gets secondary data from diaries, supporting books, documents, and other reading sources. The data analysis technique used triangulation through data reduction, data display, data conclusions. The puppet performances are both a viewing medium and a guidance medium—shows and guides based on cultural elements. The application of the Sundanese cultural values of silih asih, silih asuh, and silih asah is indirectly felt by the people who watch it, which cannot be separated from the characters or puppeteers who play the storyline of the puppet performances. Ki Dalang Wisnu Sunarya reflects the meaning of Sundanese cultural values, where the skill of a puppeteer can be proven when the puppet story has entered the content section of the guidance, such as the message of good teachings that are always conveyed.